Economic feasibility study for establishing a cultivar barley project in Lattakia Governorate - فاضل نور; إبراهيم صقر (Latakia University Journal -Biological Sciences Series, 2023)
The forage barley germination project is an industrial method for the production of green fodder that does not require agricultural land or soil, and does not occupy a large area. The cultivar barley projects have great importance and an effective impact, whether on the economic or animal levels, as the fodder barley culturing project can be conducted at a lower cost than the production of traditional fodder, which leads to a reduction in the cost of meat and dairy production amid a high standard of living and unemployment. The research aims to study the economic feasibility of cultivating fodder barley, as it is preferable to establish such projects in areas where livestock is concentrated. The descriptive approach and the case study method were adopted to conduct this study. The indicators indicate the feasibility of establishing such projects. The rentier coefficient based on the invested capital amounted to 35.75%, and based on production costs 64.78%, while the profitability coefficient based on the invested capital amounted to 32.3%, and for production costs 61.99%, and the time of recovery of the invested capital 1.52 years old. Consequently, the fodder barley breeding project is a profitable project, and it is a good alternative to imported fodder, and the research recommends a set of recommendations, the most important of which is the need to encourage livestock breeders to enter the field of fodder barley cultivation, by providing loans through village banks, development or small projects. .